Identifikasi Mata Katarak Menggunakan Arsitektur EfficientNet-B7 - ICHWAN, MUHAMMAD; REZA, MUHAMMAD DWIKI (e-Proceeding FTI, 2024)
The biggest cause of blindness in Indonesia is cataracts. Cataracts are visual impairment which is the first sign of visual impairment before glaucoma and diabetic retinopathy, therefore it is necessary to detect visual impairment before blindness occurs. With the development of artificial intelligence on computer vision, it has now been widely applied in image identification in the health sector. This study uses deep learning with the convolution neural network (CNN) method with efficientnet-b7 architecture and the update of this study using the SGD hyperparameter optimizer, learning rate 0.01 , batch size 10, epoch 10 and dropout regularization to identify cataract eyes from several experiments conducted to obtain optimal hyperparameter values. The model performance results obtained in this study with an accuracy of 94%, with a loss of 5,7, and a precision value of 1.00, a recall of 1.00 and a fi-score of 1.00. it can be concluded that the convolution neural network (CNN) method with efficientnet-b7 architecture and hyperparameters can increase the value of accuracy. Abstrak Penyebab kebutaan terbesar yang ada di Indonesia adalah katarak. Katarak merupakan gangguan penglihatan yang merupakan tanda gangguan penglihatan pertama sebelum glaukoma dan retinopati diabetes, sebab itu perlu melakukan deteksi gangguan penglihatan sebelum terjadi kebutaan. Dengan perkembangan kecerdasaan buatan terhadap computer vision saat ini sudah banyak diterapkan dalam identifikasi gambar dibidang kesehatan. Penelitian ini menggunakan deep learning dengan metode convolution neural network (CNN) dengan arsitektur efficientnet-b7 dan keterbaruan dari penelitian ini menggunakan hyperparameter optimizer SGD, learning rate 0,01 , batch size 10, epoch 10 dan dropout regularization untuk mengidentifikasi mata katarak dari beberapa percobaan yang dilakukan untuk mendapatkan nilai hyperparameter yang optimal. Hasil perfoma model yang diperoleh pada penelitian ini dengan akurasi 94%, dengan loss 5,7, serta nilai presisi sebesar 1.00, recall sebesar 1.00 dan fi-score sebesar 1.00. dapat disimpulkan bahwa metode convolution neural network (CNN) dengan arsitektur efficientnet-b7 dan hyperparameter dapat meningkatkan nilai akurasi.